Renal Arteriovenous Fistula in a Renal Transplant Recipient: A Case Report and Literature Review - Schwing, Justine (Transplant Direct, 2019)
BACKGROUND. Renal arteriovenous fistula (rAVF) is a rare complication after a total nephrectomy, with only 72 cases reported in the last literature review published in 1997. AVF has never been described in a renal transplant recipient, and the possible consequences of hemodetournement on the graft function are unknown. METHODS. We hereby reported the first case of rAVF occurring in a renal transplant recipient and analyzed all cases of postnephrectomy rAVF reported between 1997 and 2017. RESULTS. A 75-year-old woman who underwent a right nephrectomy and kidney transplant 16 years earlier, and complaining of mild exercise dyspnea, was discovered with a lumbar continuous murmur. Echocardiography showed a moderate to severe dilatation of the left ventricle, with a decreased ejection fraction. Serum creatinine was slightly raised but returned to normal value with hydration. An injected computed tomography scan demonstrated a communication between the stump of the right renal artery and inferior vena cava. Total occlusion of the rAVF was obtained with Amplatzer plug and coils placed in the distal renal stump, just upstream of rAVF. Exercise dyspnea disappeared immediately, and regression of left ventricular dilatation was objectified at 6-month echocardiography follow-up. CONCLUSIONS. Postnephrectomy rAVF is rare, frequently diagnosed late, and may be responsible for high-output heart failure by left-to-right shunt, with abdominal/lumbar bruit being the only manifestation. Renal complications concern 15% of the patients. Endovascular procedure is nowadays the treatment of choice. Occluding rAVF permits cardiac hemodynamic features and heart failure symptoms resolution.